Extra-legal abortion and post-abortion care knowledge, attitudes, and practices among obstetrician-gynecologist clinicians and medical residents in San José, Costa Rica: a qualitative study - Blake Erhardt-Ohren; Ellyn Pier; Daniel Arroyo; Whitney Cole; McKaylah Hilliard; Adriana Otero-Gonzalez; Oscar Hidalgo-Mora; Sebastian Ospina-Henao; Roger Rochat; Anna Newton-Levinson (BMC, 2023)
Abstract Background Induced abortion in Costa Rica is illegal in all cases except to save the life of the pregnant person. Despite severe restrictions to legal abortion, individuals in Costa Rica still induce abortions outside of the formal healthcare system. These individuals and those with spontaneous abortions, also known as miscarriages, occasionally need medical care for complications. In Costa Rica, an estimated 41% of unintended pregnancies end in abortion, yet there is very little published literature exploring the perspectives of healthcare providers on abortion in Costa Rica. Methods We interviewed ten obstetrician-gynecologist clinicians and five obstetrician-gynecologist medical residents in San José, Costa Rica about their beliefs and practices related to extra-legal abortion and post-abortion care (PAC) using a Spanish language in-depth semi-structured interview guide. After transcription and translation into English, analysis team pairs used a combination of deductive and inductive coding to identify themes and sub-themes within the data. Results Obstetrician-gynecologist clinicians and medical residents were aware of the presence of extra-legal abortion, and particularly, medication abortion, in their communities, but less familiar with dosing for induction. They expressed the desire to provide non-judgmental care and support their patients through extra-legal abortion and PAC journeys. Study participants were most familiar with providing care to individuals with spontaneous abortions. When discussing PAC, they often spoke about a policy of reporting individuals who seek PAC following an extra-legal abortion, without commenting on whether or not they followed the guidance. Conclusions This study contributes to a gap in research about the knowledge, attitudes, and practices of Costa Rican obstetrician-gynecologist clinicians and medical residents around extra-legal abortion and PAC. The results reveal an opportunity to train these healthcare providers as harm reduction experts, who are able to accurately counsel individuals who are seeking abortion services outside of the healthcare system, and to provide training to improve care for individuals needing PAC.